“AMERICAN EVIL” IN THE PUBLICISTIC OF DRAGOŠ KALAJIĆ - Dostanić, Dušan (Political Review, 2025)
In the article, the author examines the concept of „American evil" in the articles of the Serbian painter and publicist Dragoš Kalajić. In the first part, Kalajić’s concept of “American evil” is situated within the framework of traditionalist thought, an anti-modern current of thought. This primarily refers to the work of Julius Evola, who had a great influence on Kaljić. From a traditionalist perspective, modernity implies a project of unifying the world, from which arises a split between different moral-political orientations, which manifests itself as a conflict between the elite and the people. In the third part of the paper, the geopolitical consequences of Kalajić’s understanding of “American evil” are discussed.